Appositionsforbindelser - Schack, Jørgen (Ny forskning i grammatik, 2016)
This paper discusses the notion of apposition as accounted for in current Scandinavian grammars and studies. It is concluded that the term ‘apposition’ should be reserved for parenthetical units, i.e. syntactically independent, non-restrictive units such as Barack Obama in den amerikanske præsident, Barack Obama, leaving out constructions such as den amerikanske senator Bernie Sanders, in which the rightmost unit, Bernie Sanders, functions as the head of a noun phrase.